Author Correction: Clinical Manifestations and Ophthalmic Outcomes of Ocular Syphilis at a Time of Re-Emergence of the Systemic Infection. Issue 1 (December 2018) - Furtado, João; Arantes, Tiago; Nascimento, Heloisa; Vasconcelos-Santos, Daniel; Nogueira, Natalia; Queiroz, Rafael; Brandão, Luana; Bastos, Thaís; Martinelli, Ricardo; Santana, Rodrigo; Muccioli, Cristina; Belfort, Rubens; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.